Mechanisms of pearlite spheroidization: Insights from 3D phase-field simulations. (December 2018) - Amos, P.G. Kubendran; Bhattacharya, Avisor; Nestler, Britta; Ankit, Kumar
Abstract: Morphological evolution of eutectoid phases determine the spheroids' size and distribution post sub-critical annealing of steel. In this work, the spheroidization of the 3-dimensional cementite plates is investigated via phase-field modeling to enhance our understanding of the underlying capillary-mediated mechanisms. Since the interfacial energy plays a key role in the spheroidization process, a phase-field model which efficiently avoids any contribution of the bulk free energy in the interface is employed to recover the sharp interface solutions. It is identified that depending on the cementite aspect ratio, the spheroidization mechanism adopted by the plate, varies. In plates of smaller aspect ratios ( < 27 ), the transformation is characterized by the recession of the edges and corners, following which, the entire plate collapses into a single spheroid. However, if the plate aspect ratios are greater than 27, discontinuities set-in due to a curvature-difference between the receding edges and the flat surfaces. Such discontinuities or holes continue to evolve and coalesce during the annealing process. Our phase-field simulation-based analysis of the cementite spheroidization provides the first exposure of the spatiotemporal pathways leading to the spheroidization of cementite. A change in the evolution mechanism from the 'edge-migration regime ' to a 'discontinuities-assisted' one, is found to be responsible for the fragmentation of cementite plates. The influence of the kinetic pathways on the resulting size and spatial distribution of the spheroids are discussed. Graphical abstract: Image 1